2018
DOI: 10.1042/bsr20181099
|View full text |Cite
|
Sign up to set email alerts
|

Circulating level of fibroblast growth factor 21 is independently associated with the risks of unstable angina pectoris

Abstract: There is increasing evidence that serum adipokine levels are associated with higher risks of cardiovascular diseases. As an important adipokine, fibroblast growth factor 21 (FGF21) has been demonstrated to be associated with atherosclerosis and coronary artery disease (CAD). However, circulating level of FGF21 in patients with angina pectoris has not yet been investigated. Circulating FGF21 level was examined in 197 patients with stable angina pectoris (SAP, n=66), unstable angina pectoris (UAP, n=76), and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
1
8
1
Order By: Relevance
“…A study that investigated the role of FGF21 in SAP found higher FGF21 levels (SAP: 323.16 ± 434.66 vs. control: 266.46 ± 417.13 pg/mL; p = 0.039), similar to our study; however, multiple regression analyses showed that FGF21 levels could not be used as a marker for SAP (18). In another study, serum FGF21 levels were found higher in patients with unstable angina pectoris than in the SAP and control group, and there was no difference between serum FGF21 levels in SAP and control subjects un like to our study (19). This may be due to study design differences, heterogeneities in patients' cardiovascular risk profiles, insulin resistance, drug use, body mass index, visceral fat distribution, and gender distribution.…”
Section: Discussionsupporting
confidence: 88%
“…A study that investigated the role of FGF21 in SAP found higher FGF21 levels (SAP: 323.16 ± 434.66 vs. control: 266.46 ± 417.13 pg/mL; p = 0.039), similar to our study; however, multiple regression analyses showed that FGF21 levels could not be used as a marker for SAP (18). In another study, serum FGF21 levels were found higher in patients with unstable angina pectoris than in the SAP and control group, and there was no difference between serum FGF21 levels in SAP and control subjects un like to our study (19). This may be due to study design differences, heterogeneities in patients' cardiovascular risk profiles, insulin resistance, drug use, body mass index, visceral fat distribution, and gender distribution.…”
Section: Discussionsupporting
confidence: 88%
“…Supplementary Table 1 summarizes the patient selection criteria of these studies. Among these studies, 14 reported serum FGF21 concentration in patients with or without CVDs ( 10 23 ), 14 reported ORs or HRs of serum FGF21 concentration and incidence of CVDs ( 11 , 14 , 17 , 18 , 20 , 24 32 ), 8 reported Pearson's r of serum FGF21 concentration and vascular parameters ( 12 , 15 , 16 , 25 , 30 , 33 35 ), and 6 reported incidence of CVDs in individuals with different serum FGF21 levels ( 27 , 30 , 36 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…Three studies also provided serum FGF21 concentration of each patient in scatter plots ( 10 , 14 , 23 ) ( Supplementary Figure 1 ). Among 14 studies, 9 studies reported that serum FGF21 concentration was significantly higher in patients with CVDs, including CAD and hypertension ( 11 , 12 , 14 , 15 , 17 19 , 22 , 23 ). However, one study reported that serum FGF21 concentration was significantly lower in patients with subclinical atherosclerosis ( 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…The difference in admission values of FGF 21 between outcome groups (Table 1, Fig. 1) suggests faster elevation in the poor outcome group, although it may also partly reflect the cardiovascular risk factors preceding the cardiac arrest [28][29][30] . The association of higher FGF 21 concentrations during the first 72 h with poor 6-month outcome (Tables 3, 4, 5) suggest that the stressful process leading to FGF 21 expression fails to resolve in the poor outcome group.…”
Section: Or 95% CI P-valuementioning
confidence: 99%
“…Our findings are in line with previous data reporting elevated FGF 21 levels in general population of critical care patients 13 . The emerging role of FGF 21 as a marker of mitochondrial dysfunction 27 combined with reports of elevated FGF 21 predicting cardiovascular events [28][29][30] make cardiac arrest an especially interesting condition for studying FGF 21 due to the extreme ischaemia-reperfusion event of circulatory standstill followed by resuscitation.…”
Section: Or 95% CI P-valuementioning
confidence: 99%